STEM Module Validation: Enhancing Physics Knowledge in Prospective Teacher Education - Ibrahim, Ibrahim; Bahtiar, Bahtiar; Maimun, Maimun; Fauzi, Asri (Jurnal Ilmiah Profesi Pendidikan, 2024)
This research aims to develop and evaluate the validity of a STEM-based learning module designed to improve understanding of physics concepts for prospective teachers. This module includes various physics materials that are integrated with the STEM (Science, Technology, Engineering and Mathematics) approach and is designed to be implemented in the classroom learning process. Module validation was carried out by five experts who assessed four main aspects: accuracy of material, clarity of presentation, integration of STEM approaches, and suitability to learning objectives. The results of the analysis using Aiken's V show that this module has good validity, with the accuracy of the material getting the highest score of 0.85, followed by clarity of presentation and integration of the STEM approach which each got a score of 0.75, and suitability with learning objectives which got a score of 0.7. Based on these results, it can be concluded that this module is ready to be implemented in learning and has the potential to effectively improve prospective teachers' understanding of physics concepts.